Effect of age and sex on acenocoumarol requirements. - Arboix, M (1984)
A group of 690 patients (337 males and 353 females) on long-term acenocoumarol therapy was studied. 62.8% of the values of the prothrombin ratio were within the chosen therapeutic range (1.8 to 2.7), 21.9% were below 1.8 and 15.3% were above 2.7. The daily maintenance dose, expressed on a weight basis, was found to significantly decrease with increasing age. The daily maintenance dose taken by females was significantly higher than the dose taken by males (P less than 0.05); the differences between males and females were maximal among patients aged between 21 and 50 years, and disappeared at older ages. Two hundred and twenty-eight haemorrhagic episodes in 160 patients were recorded during a total of 7797 months of follow-up. No lethal haemorrhages were observed. The overall incidence of bleeding episodes among females (3.6%) was higher than among males (2.2%) (P less than 0.001), even if menorrhagia was excluded (P less than 0.01).